Gabapentinoid dependence syndrome: new challenges for ukrainian medicine - Omelyanovich, Vitalii (Psychosomatic Medicine and General Practice, 2025)
Introduction. The abuse of gabapentinoids, which has become widespread in our country since the start of the full-scale war, has been studied in foreign scientific medical literature for the past 15 years, and drugs classified as gabapentinoids have been among the most widely prescribed drugs worldwide in the past ten years. In Ukraine, the number of mental disorders, in particular stress-related disorders, with a predominance of anxiety-depressive symptoms, has increased significantly during the full-scale war with the Russian Federation, and at the same time, the risk of abuse of these drugs and the development of a syndrome of dependence on them has increased. This problem requires careful study and is extremely relevant, taking into account the peculiarities of the dynamics of the structure of mental morbidity in our war-torn country. Aim. To explore the current state of scientific knowledge regarding the epidemiology, pathogenesis, and clinical characteristics of gabapentinoid abuse and dependence syndrome, with subsequent assessment of the current state of knowledge on this issue and identification of future directions for scientific research. Materials and methods. The study material is data from publications reporting of research results by the epidemiology, pathogenesis, and clinical features of gabapentinoid abuse and dependence syndrome have been presented in peer-reviewed scientific publications over the past twenty years. Results. Pregabalin was introduced to the global market in 2004 as a medication recommended for the treatment of neuropathic pain, epilepsy, and anxiety disorders. However, as early as 2008, concerns were raised in the scientific literature regarding the abuse potential of pregabalin, particularly among individuals with a history of substance dependence syndrome. The exact mechanism underlying gabapentinoid abuse remains unclear. However, it is known that gabapentinoids bind with high affinity to the α2-δ1 subunit of voltage-gated calcium channels (VGCCs), with lower affinity to the α2-δ2 subunit, and no affinity to the α2-δ3 subunit. The α2-δ1 subunit is considered the primary pharmacological target of gabapentinoids, and its high affinity contributes to both their therapeutic effects and potential for misuse. According to recent scientific publications analyzing this issue in Europe, the European Medicines Agency (EMA) recorded 11,940 adverse drug reactions (ADRs) related to off-label use, misuse, or dependence on gabapentinoids between 2004 and 2015. The first case of pregabalin dependence was reported in 2010 in the American Journal of Psychiatry. Over the past 15 years, research into gabapentinoid abuse and dependence syndrome has continued; however, the number of peer-reviewed publications remains limited. Most reported cases of pregabalin misuse involve individuals with a history of psychoactive substance use. Similarly, epidemiological studies have confirmed evidence of abuse. Researchers emphasize that male gender and a history of polydrug use may represent risk factors for the development of addictive behaviors associated with pregabalin. Conclusions. Current studies on the epidemiology, clinical features, and effective treatment approaches for gabapentinoid misuse and dependence are limited and lack systematic organization. Existing research highlights the high risk associated with prescribing gabapentinoids to individuals—primarily males—who abuse psychoactive substances, have a history of substance use disorders, or are currently diagnosed with such conditions. Given the characteristics of war veterans with post-traumatic stress disorder—particularly those who have sustained severe injuries, such as amputations—the issue of non-medical gabapentinoid use is of particular concern for Ukrainian medicine and warrants further in-depth investigation.